On the Iterative Methods of Linearization, Decrease of Order and Dimension of the Karman-Type PDEs - Krys'ko, Vadim Anatolevič; Awrejcewicz, Jan; Pavlov, S.P.; Zhigalov, M.V. (My University, 2014)
Iterative methods to achieve a suitable linearization as well as a decrease of the order and dimension of nonlinear partial differential equations of the eighth order into the biharmonic and Poisson-type differential equations with their simultaneous linearization are proposed in this work. Validity and reliability of the obtained results are discussed using computer programs developed by the authors.